2006
DOI: 10.1159/000097520
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Sagittal Craniosynostosis Using a Novel Parietal Bone Fixation Technique: Results over a 10-Year Period

Abstract: Isolated sagittal synostosis is a common form of craniosynostosis affecting roughly 1 in 5,000 children at birth. This results in a scaphocephalic head shape with a characteristically elongated anterior-posterior dimension and narrowed biparietal diameter. We present our experience with the correction of scaphocephaly due to sagittal synostosis using cranial vault reconstruction with a novel form of parietal bone fixation in 21 patients over 10 years. The medial fixation results in a hinging effect whereby tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In later years, surgery consisted of various methods of craniotomy and remodeling that are still the most frequently applied technique [10,24,25,26]. Distraction osteogenesis was introduced in the mid- to late-1990s, and appeared to offer advantages in that: bone fusion is more effectively accomplished, the operation time is shortened, and transfusion volume is decreased [2,3,4,7,9,11,12]. However, the risks arising from the relatively shortened operation time and decreased transfusion volume meant distraction osteogenesis was still not safe for infants and young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In later years, surgery consisted of various methods of craniotomy and remodeling that are still the most frequently applied technique [10,24,25,26]. Distraction osteogenesis was introduced in the mid- to late-1990s, and appeared to offer advantages in that: bone fusion is more effectively accomplished, the operation time is shortened, and transfusion volume is decreased [2,3,4,7,9,11,12]. However, the risks arising from the relatively shortened operation time and decreased transfusion volume meant distraction osteogenesis was still not safe for infants and young children.…”
Section: Discussionmentioning
confidence: 99%
“…However, all procedures to date have still been complicated, taken a long period of time, and shown a marked loss of blood (and hence increased volume of transfusions), and a greater overall risk in infants and young children [1,9,10]. The mean operation times for classical craniotomy/remodeling and distraction osteogenesis have been reported to range from 150 to 441 and from 183 to 336 min, respectively, and the mean volume of transfused blood ranged from 100 to 426 and 178 to 350 ml, respectively, indicating a high risk for children undergoing classical craniotomy and remodeling [3,4,6,9,11,12]. Although there are few reports to date which have described repeat surgery after distraction osteogenesis, it has been indicated that repeat surgery occurs in 6.7–40% of patients who received classical craniotomy and remodeling, and therefore a new and effective surgical method is necessary [10,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the proposed treatment, we considered the main surgical techniques to be the synostectomies (removal only of the sagittal suture), springs and cranial reconstruction with its variants [9,10,11,12,13,14,16,17,18,19]. Only those children for whom the technique proposed by D. Renier [9] was performed were included in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Scaphocephaly, which is the most common type of craniosynostosis, accounts for approximately 40 to 60% of the isolated suture synostosis, and occurs in 1 in 5,000 children at birth 2,5,8,18,26,27) . Numerous techniques have been used to correct scaphocephaly in infants including bilateral strip craniectomy, wide-strip craniectomy, the π procedure, total vertex craniectomy, endoscopic craniectomy and cranial vault remodeling with parietal flap cranioplasties 3,4,6,7,10,11,[13][14][15]17,18,20,22,23,[25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques have been used to correct scaphocephaly in infants including bilateral strip craniectomy, wide-strip craniectomy, the π procedure, total vertex craniectomy, endoscopic craniectomy and cranial vault remodeling with parietal flap cranioplasties 3,4,6,7,10,11,[13][14][15]17,18,20,22,23,[25][26][27][28][29][30] . However, there is still debate over which method of the surgery is most appropriate for the treatment of scaphocephalic infants.…”
Section: Introductionmentioning
confidence: 99%